Pengaruh Komunikasi Keluarga dan Kemampuan Awal IPA terhadap Prestasi Belajar IPA - Hasbullah Hasbullah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2012)
The purpose of this study was to determine the effect of family communication and early knowledge of science to learn science achievement. The method used is survey method. Samples were taken as many as 102 students with a simple random technique. Data analysis using correlation and regression techniques. The results showed: 1) there is a positive influence of family communication and knowledge of early science together on science learning achievement, 2) there is a positive influence of family communication on science learning achievement, 3) no prior knowledge of the influence of science on science learning achievement.